Tibio-talo-calcaneal arthrodesis with compressive retrograde intramedullary nail - Zaourak, Javier; A., Paz; J., Chahla; D., Arroquy; F., Vago Anaya; E., Loncharich (Tobillo y Pie, 2016)
Objective: The purpose of this study was to assess the clinical and functional results, postoperative complications, time to fusion, union rate and axis correction in patients undergoing tibio-talo calcaneal arthrodesis with compressive retrograde intramedullary nail. Methods: Fourteen tibiotalo-calcaneal arthrodesis with compressive retrograde intramedullary nail were performed in 13 patients. The clinical and functional results were evaluated through the AOFAS scale both preoperative and after an average of 2 years of follow-up. Complications were assessed based in our clinical records. Radiographic alignment, time to fusion and union rate was recorded. Results: The AOFAS average improvement was 45,75 points (pre surgical average of 27,15 points and post surgical average of 72,9 points). Two major complications were registered (two deep infections) and one minor complication (locking screws loosening). Tibio-talar unión was achieved in 100% of cases. The mid deformity correction in varus was 8,86º and 13,6º in valgus. Conclusions: The tibio-talo-calcaneal arthrodesis with compressive retrograde intramedullary nail is an effective technique to achieve a significant clinical improvement, with good union rates and adequate ankle and hind-foot deformity correction.